Kajian Finansial Usaha Pengolahan Gula Aren di Kecamatan Padang Batung Kabupaten Hulu Sungai Selatan - Ani Yuliana; Fardianah Mukhyar; Abdullah Dja’far (Universitas Lambung Mangkurat, 2011)
Palm sugar processing business is an important source of livelihood for the craftsmen in the Hulu Sungai Selatan District, Padang Batung sub-District, because almost the entire villagers in this district there are palm sugar craftsmen. But, the continuity of their business might be not running well because there is no rejuvenation as well as cultivation of crops producing palm sap as the main raw material manufacture of palm sugar. In addition, the fuel used, in the form of firewood, is also more difficult to obtain. This study aims were to determine the performance of palm sugar processing business in terms of financial aspects, namely: the cost, revenue, income and business profits, break-even point (BEP) and the value added derived from palm sugar processing business. Further, the study also identified the problems faced by craftsmen. Results showed that palm sugar processing business has been conducted for generations by craftsmen, using traditional methods, yet still provide benefits to producers. Break-even point (BEP) could be exceeded within a week. Problems at the level of craftsmen were the availability of raw materials, wood as fuel and the long outpouring of working time for production. Processing technology that can save labor as well as business development is needed.